Synthesis of 2, 2-difluoro-3H-benzothiophen-3-ol via a difluorocarbene insertion reaction, investigating the scope for further derivatization. Issue 16 (18th August 2019) - Rodrigues, Clarence; Hall, Roger G.; Montgomery, Mark; Yang, Xiuhua; Xiang, Yong; Lu, Long; Pal, Sitaram; Manjunath, Bhanu N.
Abstract: A simple, and efficient synthesis of 2, 2-difluoro-3 H -benzothiophen-3-ol using readily available sodium chlorodifluoroacetate (SCDA) is reported. We also explore new chemistry of these difluoro compounds. The salient feature of this approach includes operational simplicity and offers potential access to synthetically challenging building blocks for further elaboration. Functional group transformations of this new heterocycle are also presented. Graphical Abstract: